Sex Differences and Bone Metastases of Breast, Lung, and Prostate Cancers: Do Bone Homing Cancers Favor Feminized Bone Marrow? - Farach-Carson, Mary C.; Lin, Sue-Hwa; Nalty, Theresa; Satcher, Robert L. (Frontiers in Oncology, 2017)
Sex-associated differences in bone metastasis formation from breast, lung, and prostate cancer exist in clinical studies, but have not been systematically reviewed. Differences in the bone marrow niche can be attributed to sexual dimorphism, to genetic variations that affect sex hormone levels, or to the direct effects of sex hormones, natural or exogenously delivered. This review describes the present understanding of sex-associated and sex hormone level differences in the marrow niche and in formation of bone metastasis during the transition of these three cancers from treatable disease to an often untreatable, lethal metastatic one. Our purpose is to provide insight into some underlying molecular mechanisms for hormonal influence in bone metastasis formation, and to the potential influence of sexual dimorphism, genetic differences affecting sex assignment, and sex hormone level differences on the bone niche and its favorability for metastasis formation. We reviewed publications in PubMed and EMBASE, including full length manuscripts, case reports, and clinical studies of relevance to our topic. We focused on bone metastasis formation in breast, lung, and prostate cancer because all three commonly present with bone metastases. Several clear observations emerged. For breast cancer bone metastasis formation, estrogen receptor (ER) signaling pathways indicate a role for ER beta (ERβ). Estrogen influences the bone microenvironment, creating and conditioning a favorable niche for colonization and breast cancer progression. For lung cancer, studies support the hypothesis that females have a more favorable bone microenvironment for metastasis formation. For prostate cancer, a decrease in the relative androgen to estrogen balance or a “feminization” of bone marrow favors bone metastasis formation, with a potentially important role for ERβ that may be similar to that in breast cancer. Long-term estrogen administration or androgen blockade in males may feminize the bone marrow niche to one more favorable for bone metastases in prostate cancer. Administration of androgens in females, especially combined with mastectomy, may reduce risk of developing bone metastatic breast cancer. We conclude that it should be considered that females, those with female-leaning genetic variations, or hormonal states that feminize the bone marrow, may offer favorable sites for bone metastases.